Theology, Plain and Simple: Biblical Hermeneutics, Language Philosophy, and Trinitarianism in the Seventeenth Century - Poole, Kristen (Reformation, 2019)
This essay demonstrates how the hermeneutic debates of the sixteenth century continued to thrive well into the seventeenth. In particular, it considers how biblical hermeneutics made their way into perfect or universal language schemes. In a number of texts (from the pamphlets of an eccentric religious radical to the measured treatises of ecclesiastical authorities), authors pushed the early reformers' interest in plain and simple language into schemes which purported to create a direct relationship of signifier and signified. While perfect/universal language schemes have been studied extensively by historians, the degree to which these texts are situated within long-running exegetical debates of the Reformation has largely been overlooked. Moreover, such language schemes were interlinked with theology - particularly trinitarian theology, as is exemplified in the writings of John Biddle (c. 1615-62). Studying the interconnection of perfect language and trinitarian theology reveals the imbrication of semiotics, epistemology, and theology in seventeenth-century England.